2017
DOI: 10.1590/1678-992x-2016-0242
|View full text |Cite
|
Sign up to set email alerts
|

Biochar from different residues on soil properties and common bean production

Abstract: The production of biochar from organic residues promises to be an interesting strategy for the management of organic waste. To assess the effect of biochar on soil properties and the production and nutrition of common bean (Phaseolus vulgaris L.), three simultaneous experiments were conducted in a greenhouse with different biochar from organic residues (rice husk, sawdust, and sorghum silage) used as filtration material for swine biofertilizer. In ), arranged in a completely randomized design, with four repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 19 publications
5
22
2
5
Order By: Relevance
“…As shown in Figure 1A, pH practically did not vary in the soil without biochar, however, the biochar applied to the soil increased soil pH in the two layers analyzed (top and base), corroborating Yuan and Xu (2012), and Silva et al (2017) who observed an increase in pH of the soil, considering the positive effect of biochar, particularly in acid soils. However, more significant changes were observed at the top whose calculated maximum pH value reached 8.22 applying 29.28 t ha -1 ( Figure 1A).…”
Section: Resultssupporting
confidence: 76%
“…As shown in Figure 1A, pH practically did not vary in the soil without biochar, however, the biochar applied to the soil increased soil pH in the two layers analyzed (top and base), corroborating Yuan and Xu (2012), and Silva et al (2017) who observed an increase in pH of the soil, considering the positive effect of biochar, particularly in acid soils. However, more significant changes were observed at the top whose calculated maximum pH value reached 8.22 applying 29.28 t ha -1 ( Figure 1A).…”
Section: Resultssupporting
confidence: 76%
“…On the other hand, the great quantity of K obtained because of OMSW-derived BC could result in reduced plant uptake of Ca, Mg, and P by an antagonistic effect [47, 48]. Contrary to our results, several reports found increases in the plant content of nutrients [44, 49]. The discrepancy between our data and that of other studies could be explained because of varying soil characteristics and feedstock used to produce BCs.…”
Section: Resultscontrasting
confidence: 99%
“…The high content of soil exchangeable basic cations in the high pyrolysis-temperature BC-treated soil could be explained by the increasing content of BC ash. Several other researchers have explained the improvements in the exchangeability of soil cations because of the presence of ashes in BC, which contain high levels of oxides and hydroxides of alkali cations [44].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in soil pH values may be explained by the presence of ashes in the BioC. Ashes are rich in oxides and hydroxides of alkali metals, which are easily dissolved and react rapidly with the soil, thereby increasing its pH [48]. These results are consistent with Mierzwa-Hersztek et al [49], whose research showed that alkaline substances are easily released from BioC.…”
Section: Effect Of Bioc Addition On Soil Phsupporting
confidence: 80%